Numerical and experimental investigations of two span prestressed concrete beams - Bhargava R.; Pathak K.K.; Akhtar S. (My University, 2025)
Modern structural engineering tends to progress towards more economical structures through gradually improved methods of design and the use of high strength materials. Such developments are particularly important in the field of reinforced concrete; the limiting features of ordinary reinforced concrete have been largely overcome by the development of prestressed concrete. The external post-tensioning technique has been commonly used in the construction field because external prestressing tendon can easily be designed to be replaceable, de-stressable and re-stressable. In this paper the displacement behaviors of double span prestressed concrete beams have been studied numerically and experimentally. Six beams are cast and experimented. The experimental results are compared with finite element analysis results and loss due to friction and anchorage slipis also calculated. The proposed approach offers a useful tool for calculation of realistic friction and anchorage losses in a simplified manner.